The Physical Parameters of Athenian Democracy. (2019) - Pritchard, David M.
Abstract: This article investigates the physical parameters of Athenian democracy. It explores the collective-action problems that these parameters caused and settles debates about them that R. G. Osborne famously provoked. Classical Athens was ten times larger than an average Greek state. Fourth-century Athenians were ten times more numerous. These parameters significantly contributed to the success of Athenian democracy. Athens could field more combatants than almost every other Greek state. With such huge manpower reserves individual Athenians had to fight only every few years. Nevertheless, this huge population also caused collective-action problems. Attica's farmers could not grow enough to feed them. The Athenians never had adequate personnel nor recordkeeping centrally to administer so many citizens over such a large territory. Yet they found effective means at home and abroad to overcome these collective-action problems.